Influences and Barriers on Physical Activity in Pediatric Oncology Patients - Yelton, Larrilyn; Forbis, Shalini (Frontiers in Pediatrics, 2016)
Objectives: To determine the influence of family, peers, school, and physicians on exercise in pediatric oncology patients and evaluate the barriers to physical activity levels in this population. Methods: A search of PubMed and Google Scholar resulted in 12 related articles. The articles were assessed for the influence of school systems, family, peers, self-efficacy, and physicians on exercise. Additionally barriers and interventions to physical activity were also assessed. Limitations and research methodologies of each article were also evaluated. Results: Many school systems were unsure of expectations in regards to physical activity for their returning students with cancer. Most schools acknowledged willingness to increase exercise for these students; however, there is a communication gap between the medical field and the school system on what expectations should be. Family is associated with increased physical activity levels and healthier diets in this population with children preferring mothers as exercise partners more than fathers. While physician interventions have been shown to positively impact physical activity, it has been reported that physicians are not engaging in exercise counseling with their patients. Conclusion: Several issues and barriers related to physical activity in pediatric oncology population were identified. Studies have demonstrated it is feasible to increase physical activity and self-efficacy in this population. Further research is needed to better understand and quantify these issues as well as further test the interventions that have been suggested in this review and have been successful in other pediatric populations.